A bill to prevent fraudulent conveyance of property, and for other purposes (House doc. (North Carolina. General Assembly. House of Commons), 1852)
1852 North Carolina House bill to prevent the fraudulent conveyance of property by recording the time the debtor was served with a writ of ca sa., and that property then owned by the debtor may be bound under the writ for the creditors' benefit. The bill also provided the procedure to use in these cases.